Resistance and Its Potential. (June 2020) - Muth, William
Resistance—political, physical, or philosophical—emerges in thresholds of contact where the "sides" engage, and sometimes one side gives way to the other. This study works in the thresholds of political resistance and an unsettled philosophical stance to examine a singular event in which the author's intentional being in the protest "gave way." It attends to two incompatible notions of subjectivity—an oriented/intentional lived subjectivity that is potentially available to, and claimed by, human experience and post-intentional, posthuman subject assemblages that are not accessible to human experience—to examine the potential of resistance for both civil disobedience and post-phenomenological qualitative inquiry.